D-Dimer Levels and Traditional Risk Factors Are Associated With Incident Hypertension Among HIV-Infected Individuals Initiating Antiretroviral Therapy in Uganda. (1st December 2016) - Okello, Samson; Asiimwe, Stephen B.; Kanyesigye, Michael; Muyindike, Winnie R.; Boum, Yap; Mwebesa, Bosco B.; Haberer, Jessica E.; Huang, Yong; Williams, Kenneth; Burdo, Tricia H.; Tracy, Russell P.; Bangsberg, David R.; et al.
Abstract : Objectives: We sought to describe blood pressure (BP) changes after antiretroviral therapy (ART) initiation and evaluate the association of markers of inflammation with incident hypertension in a cohort of HIV-infected individuals in Uganda. Methods: We used mixed effects linear regression to model changes in systolic BP over time among a cohort of HIV-infected individuals initiating ART in Uganda. After exclusion of participants with preexisting hypertension, we identified participants with normal BP throughout follow-up (controls) and those with elevated BP on ≥3 consecutive visits (cases). Before ART initiation, participants had testing for interleukin 6, kynurenine/tryptophan ratio, lipopolysaccharide, soluble CD14, soluble CD163, and D-dimer and those with viral suppression at 6 months during ART had repeat tests. We fit logistic regression models to estimate associations between biomarkers and risk of incident hypertension. Results: In the entire cohort, systolic BP increased by 9.6 mm Hg/yr (95% CI: 7.3 to 11.8) in the first 6 months of ART, then plateaued. Traditional factors: male gender (adjusted odds ratio (AOR) 2.76, 95% CI: 1.34 to 5.68), age (AOR 1.09, 95% CI: 1.04 to 1.13), overweight (AOR 4.48, 95% CI: 1.83 to 10.97), and a CD4 count <100 cells (AOR 3.08, 95% CI: 1.07 to 8.89) were associated with incident hypertension. After adjusting for these, D-dimer levels at month 6 were inversely associated with incident hypertension (AOR 0.61, 95% CI: 0.37 to 0.99). Although not significant, similar associations were seen with sCD14 and kynurenine/tryptophan ratio. Conclusion: BP increases early after ART initiation in Ugandans. Traditional risk factors, rather than immune activation, were associated with incident hypertension in this population.